PERLINDUNGAN HUKUM NASABAH KPR BERSUBSIDI FLPP DENGAN AKAD MURABAHAH BIL WAKALAH ATAS RUMAH YANG BELUM SIAP HUNI: STUDI PADA PT BTN KANTOR CABANG PEMBANTU SYARIAH SETIA BUDI MEDAN - Efendi Rangkuti, Khairunnisya; Sembiring, Idha Aprilyana; Barus, Utary Maharani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
BTN Syariah KCP Setia Budi Medan is one of the Islamic financial institutions involved in implementing the government's Housing Financing Liquidity Facility (FLPP) program, offering the KPR BTN Sejahtera Syariah iB product based on a murabahah bil wakalah contract. In practice, the financing of housing units that are not yet deemed habitable, as they lack essential infrastructure, facilities, and public utilities (PSU) as required by prevailing laws and regulations. This study aims to analyze the conformity between applicable regulations and field practices, examine the legal consequences of such violations, and assess the legal protection available to affected customers. The results of the study indicate that the implementation of the murbahah bil wakalah contract at BTN Syariah KCPS Setia Budi Medan violates OJK Regulation Number 13/POJK.03/2021 concerning the Implementation of Bank Products and the DSN- MUI Fatwa Number 04/DSN- MUI/IV/2000 on Murabahah. The legal implications of implementing FLPP subsidized housing financing through murabahah bil wakalah contracts for uninhabitable housing constitute an unlawful act, as it contravenes Article 14 of Government Regulation No. 12 of 2021, Article 21 of BP Tapera Regulation No. 9 of 2021, and Articles 16 and 18 of OJK Regulation Number 6/POJK.07/2022. Moreover, the contract clauses in the murabahah bil wakalah agreement contain exoneration clauses that violate Article 18 of Law Number 8 of 1999. According to Article 20 of the murabahah bil wakalah agreement with BTN KCPS Setia Budi Medan, customers may pursue their rights through deliberation involving the bank, the customer, and the developer. If no agreement is reached, the matter may be resolved through litigation.